Cooperation of Farmers and Middlemen: Epistemological Studies’ Perspective of Antonio Gramsci's Theory of Hegemony - Siti Fatimah; Kosim Kosim; Abas Hidayat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The cooperation system between farmers and Middlemen is forced because the Middlemen made a unilateral cooperation system. The farmers are powerless because they need capital and income to meet the needs of their families. This research will question what kind of cooperation system was built by farmers and Middlemen and how the farmers' attitude to unilateral decisions made by the Middlemen. The author conducted field research using a qualitative approach with a grounded research method. The primary data sources are farmers in Cirebon, Indonesia. Technically, digging up data through in-depth interviews, observations in rice fields during harvest, and focus group discussions. The cooperation system was analyzed using Antonio Gramsci’s hegemony theory. The research results are as follows: 1) The Middlemen make a profit-sharing agreement with the farmer. Farmers get loans for land rent, seeds, and planting costs. Paying debt after harvest, and farmers have to sell their crops to Middlemen. 2) Middlemen usually misbehave by lowering prices unilaterally in the middle of the cooperation process. 3) If conditions like this are analyzed using Antonio Gramsci’s theory of hegemony, then the consciousness, reason, energy, and results of the farmers are hegemonized by Middlemen.